Effective elastic characteristics of honeycomb sandwich composite shells made of generally orthotropic materials - Saha, Gobinda; Kalamkarov, Alexander L.; Georgiades, Tasos (My University, 2007)
This paper works on the analytical development of the method of two-scale asymptotic homogenization. The technique is used to determine the effective elastic stiffnesses of hexagonal honeycomb-cored structural sandwich composite shells made of generally orthotropic materials. Orthotropy of the constituent materials leads to much more complex unit-cell problems and is considered in the present paper for the first time. At first, a 3D-to-2D general shell model based on a set of unit-cell problems is derived. This is followed by the exploitation of the model to the derivation of analytical estimate formulae; used to calculate the force and moment resultants present in the sandwich shell structure. The implication of the general shell model is further indicated by calculating similar design characteristics for a three-layered composite sandwich panel reinforced with hexagonal and triangular shaped cellular core made from the generally orthotropic material.
Keywords: Micromechanics; Honeycomb structures; Elasticity